An Approach to The Understanding of “Religious Experiences” - Muhammad Bagir (Sekolah Tinggi Agama Islam Sadra, 2011)
In the old days, theology was almost a purely internal religious matter. Ilmu Kalam or Islamic Theology – although this term does not fully signify the meaning of Ilmu Kalam; has been focusing mainly on “internal religious issues” namely; on God and His attributes, on prophethood and the characteristics of prophecy and the resurrection and other issues related to beliefs. But as time goes by and the different parts of the world come into contact with each other; not only merchandises were imported and exported but ideologies and religious beliefs were in no way excluded. With the advent of the modern era since the renaissance, it seems that all things that are religious are considered as an obstacle for the rise of humanism in the whole realm of existence.